Regeneration of Pain, Touch, Cold, and Warmth, sensations in split thickness human skin grafts in adults (A clinical study) - Hatef., Mohammed B.; Kamal, Ahmed, M.; Sahan, Abbas M. (AL-Kindy College Medical Journal, 2013)
Back ground: Skin grafting is the most common form of reconstructive surgery, and regeneration of sensations in skin grafts is a complex process influenced by many factors such as , the thickness of the graft, the depth of the grafted bed, meshing of the graft, the condition of the bed and the surrounding area. So many studies performed on this subject, some of them clinically based on subjective type of sensation tests, and others histological to detect the presence of nerve fibers in the grafted skin Objectives: To detect return of sensations to split thickness skin grafts by clinical methods. Methods: From Oct. 1995 to Oct. 2010, a clinical prospective study performed in Al wasity Hospital for reconstructive surgery, Hilla teaching General Hospital, and Al kindy teaching General Hospital on recovery of sensations in human split thickness skin grafts on 200 patients, 400 grafts. There were 120 male, 80 female patients, there ages ranged from20 -61 years with mean of 28 years. The regeneration of sensation of pain, touch, cold, and warmth, was studied with the usual clinical methods. We studied; different graft thicknesses, depth of graft beds, meshing of the grafts, grafts on early and late wound excisions Results: in our study the regeneration of sensations occurred in the following order; pain, touch, cold , warmth, and has been found to extend over a period of 16days to 3 months, and sensations improve with time but never recover completely even after several years. Conclusion: The recovery of sensation of grafted skin is a complex process that is influenced by many factors; some of them are related to the graft, to the recipient bed, to the patient as a whole, and occurs if the graft is applied on a sufficiently innervated bed.